2019
DOI: 10.1073/pnas.1900613116
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of atmospheric atomic bromine leading to mercury and ozone depletion

Abstract: Bromine atoms play a central role in atmospheric reactive halogen chemistry, depleting ozone and elemental mercury, thereby enhancing deposition of toxic mercury, particularly in the Arctic near-surface troposphere. However, direct bromine atom measurements have been missing to date, due to the lack of analytical capability with sufficient sensitivity for ambient measurements. Here we present direct atmospheric bromine atom measurements, conducted in the springtime Arctic. Measured bromine atom levels reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 59 publications
(85 reference statements)
4
91
1
Order By: Relevance
“…Although our models are not able to reproduce ODEs at all spatial scales, the success of the models in capturing ODEs and BEEs (e.g., at a spatial scale >~500 km) gives additional evidence for the proposed mechanism of SSA production (as well as acting as a source of bromine) from blowing snow on sea ice (Yang et al, 2008;. Therefore, we 30 may predict that changes in sea ice extent and type in a warming climate will influence Arctic boundary layer chemistry and Arctic climate, including the deposition of atmospheric mercury to the surface (Wang et al, 2019).…”
Section: Times Antarcticmentioning
confidence: 70%
“…Although our models are not able to reproduce ODEs at all spatial scales, the success of the models in capturing ODEs and BEEs (e.g., at a spatial scale >~500 km) gives additional evidence for the proposed mechanism of SSA production (as well as acting as a source of bromine) from blowing snow on sea ice (Yang et al, 2008;. Therefore, we 30 may predict that changes in sea ice extent and type in a warming climate will influence Arctic boundary layer chemistry and Arctic climate, including the deposition of atmospheric mercury to the surface (Wang et al, 2019).…”
Section: Times Antarcticmentioning
confidence: 70%
“…stable Arctic boundary layer is decoupled from convective exchange with the free troposphere (Moore et al, 2014;Seabrook et al, 2011;Wang et al, 2019). Furthermore as boundary layer O3 reaches very low levels (<4 ppbv), BrO production via R3 530 is suppressed and atomic Br becomes much more abundant than BrO (Neuman et al, 2010;Wang et al, 2019), such that satellites would not necessarily observe co-located O3 depletion and enhanced BrO VCDtropo.…”
Section: Discussionmentioning
confidence: 99%
“…convective exchange with the free troposphere (Custard et al, 2017;Peterson et al, 2015Peterson et al, , 2017Pratt et al, 2013;Wang et al, 2019). Fig.…”
Section: Comparison To Hourly Surface O3 Observationsmentioning
confidence: 99%
“…In polar regions, GEM can be quickly oxidized by reactive bromine species and its concentration reduction are well correlated with enhanced GOM concentrations [47][48][49][50]. However, during the GEM depletion events that were observed at the Grand Bay site, GOM and PBM concentrations were very low, with a mean concentration of 0.6 pg m −3 for GOM and of 3.4 pg m −3 for PBM ( Figure 13).…”
Section: Gem Depletion Eventsmentioning
confidence: 98%
“…During this event, standard additions of GEM were conducted and the recovery of the GEM standard additions at the inlet on the tower remained relatively constant, which indicated that the observed GEM depletion was not a measurement artifact and it was not due to any potential losses of GEM in the ambient air through the sampling system. In polar regions, GEM can be quickly oxidized by reactive bromine species and its concentration reduction are well correlated with enhanced GOM concentrations [47][48][49][50]. However, during the GEM depletion events that were observed at the Grand Bay site, GOM and PBM concentrations were very low, with a mean concentration of 0.6 pg m −3 for GOM and of 3.4 pg m −3 for PBM ( Figure 13).…”
Section: Gem Depletion Eventsmentioning
confidence: 98%